Increasing Sustainable Post Pandemic Economic Activities in Coastal Fishing Ports - Kristiyanti, Mariana; Fauziningrum, Endah (Journal of Economics and Public Health, 2022)
Sea transportation is an important means of supporting the economy and welfare distribution in remote areas in Indonesia, but, many areas do not yet have adequate sea transportation facilities. This is one of the economic development problems that needs to be considered. In order to support economic development in those areas, it is necessary to plan and develop port facilities as a support to sea transportation services. With the lack of port facilities infrastructure, it affects the flow of port traffic and becomes difficult to develop. The current Pandemic condition is a challenge considering that fishing activities are very disrupted, but it does not dampen the desire to be able to solve problems in developing coastal fishing ports which are the main source of people living in coastal areas. This research aims to develop a coastal fishing port into a modern port. In addition, this research was also carried out to support the improvement of the economic activities of fishing communities in coastal areas. The type of data used is qualitative data while the data collection method used are interview, observation and literature study. The results show that the economic activities of coastal communities in the pandemic era require management policy. It is needed by placing economic interests in proportion to environmental interests, both in the short and long term. Community development strategies can be carried out through two approaches, they are, structural and non-structural.